2008
DOI: 10.1039/b809578g
|View full text |Cite
|
Sign up to set email alerts
|

A photochemical study on the blue dye indigo: from solution to ancient Andean textiles

Abstract: The degradation of indigo and its water soluble derivative indigo carmine was investigated under light excitation in the presence and absence of molecular oxygen in solution (homogeneous) and gels (heterogeneous) media. Collagen and carboxymethylcellulose (CMC) aqueous gels were chosen to simulate a natural textile environment, wool and cotton, respectively. Isatin was found to be the major degradation product of indigo. In solution, the photodegradation quantum yields (Phi(R)) were in the order of 10(-4), wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
53
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 80 publications
(60 citation statements)
references
References 31 publications
6
53
1
Order By: Relevance
“…46 It was found that such molecular cleavage resulted in the production of lower molecular weight species, mainly isatin. 42,46 In the present investigation, the H 2 O 2 /UV degradation of indigotin in DMSO solution progressed rapidly, and consistent with previous findings in the literature, isatin was produced as the major degradation product. It is suggested that isatin was produced as ÁOH addition occurred to the central double bond of indigotin upon H 2 O 2 /UV degradation ( Figure 11).…”
Section: Discussion On the Degradation Of Dyes In Solutionsupporting
confidence: 92%
“…46 It was found that such molecular cleavage resulted in the production of lower molecular weight species, mainly isatin. 42,46 In the present investigation, the H 2 O 2 /UV degradation of indigotin in DMSO solution progressed rapidly, and consistent with previous findings in the literature, isatin was produced as the major degradation product. It is suggested that isatin was produced as ÁOH addition occurred to the central double bond of indigotin upon H 2 O 2 /UV degradation ( Figure 11).…”
Section: Discussion On the Degradation Of Dyes In Solutionsupporting
confidence: 92%
“…[25][26][27] However, in these works the yields of degradation are not reported and keto indigo is known to be a stable molecule that only suffers some degradation in extreme conditions, such as the presence of nitric acid or under light excitation, and even at these conditions with very low quantum yields of reaction (10 À4 or lower). [28] The significantly different photophysical behaviour shown by the leuco forms strongly suggest that this form is more prone to reactions and subsequently to degradation.…”
Section: Resultsmentioning
confidence: 98%
“…Textiles recovered from archaeological excavations allowed the identification of natural dyes used for colouring, such as purple and red insect dyes identified in Roman Egyptian archaeological textiles [2], or the application of indigo for the production of the Paracas mantles used for covering the deceased [3]. Other natural dyes were used for textile decoration, like cochineal and brazilwood lakes.…”
Section: Introductionmentioning
confidence: 99%